Simon Rattle: The Making of a Conductor - Kenyon, Nicholas 1951- Sir (London Faber and Faber, 1989)
The book includes interviews with family, friends and colleagues as well as with Rattle himself.
Keywords: Rattle, Simon -- 1955-; Music history; Conductor; Interview